Keanekaragaman Tumbuhan Pekarangan dan Pemanfaatannya Untuk Prasarana Pembelajaran Di Sekolah PSKD 1 Jakarta Sebagai Salah Satu Usaha Konservasi - Marina Silalahi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
The research on the diversity of yard plants and their utilization for learning infrastructure at the PSKD 1 school in the Jakarta to the conservation efforts. in The research was conductedat the January-April 2018through two step arethe exploration in the yard of PSKD 1 School 1 and interviews with thebiology teachers and Deputy Head. The plants found were recorded in local names, habits, and use. The data obtained were processed by using descriptive statistics. There were 93 local names of plants found in the PSKD 1Schoolyard in the Jakarta, which consisting of 86 species names belonging to 67 genus and 33 families. The Araceae, Asparagaceae, Arecaceae, and Moraceae are the families with the largest number of species are 14, 10, 5 and 5 species respectively. In the biology study the plants in the yard are utilized in the biodiversity, ecological and plant morphology materials. The pinus (Pinus merkussi) and jamblang (Syzygium cumini) are the plants that to be difficult to find in Jakarta, but still found in the PSKD school yard. To maintain the sustainability of the plant needs to be multiplication through seeding and cuttings. Keywords: Shcool yard, PSKD, Pinus merkussi, Syzygium cumini